Uji Sensivitas Perasaan Daun Ceremai (Phyllanthus Acidus (L)Terhadap Pertumbuhan Escherichia Coll Dan Staphylococcus Aureus - Nurul Utami Halimsyah (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
Bacteria are single-celled microorganisms, have strong walls and a fixed shape. The bacteria Escherichia coli is a bacteria commonly found in the opportunistic human colon as normal flora that can menyebapkan infection in the gut eg diarrhea and also its ability to cause infection in the tissue. Staphylococcus aureus can be found on the surface of the skin as normal flora, especially around the nose, mouth, genitals and around the anus and can cause wound infections usually abscess is a collection of pus or fluid in the tissue due to infection The purpose of this study is to determine whether there is influence the growth of bacteria Escherichia coli and Staphylococcus aureus in the juice of the leaves ceremai (Phyllanthus acidus L) at a concentration of 100%, 80%, 60 % , 40% and 20% The method used in this study are Merode experiments conducted experiments on concentration in the water feeling ceremai leaf (Phyllanthus acidus (L) on the growth Eschrichia coli and Staphylococcus aureus in vitro. The results showed that the leaf juice ceremai not inhibit the growth of bacteria Escherichia coli and Staphylococcus aureus in the juice of the leaves ceremai (Phyllanthus acidus L) at a concentration of 100 %, 80%, 60% 40% and 20 % . Based on these stucies are expected to communities that no longer consume freshly ceremai leaves, because water leaves feeling ceremai not to inhibit the growth of bacteria Escherichia coli and Staphylococcus aureus.